Seasonal variation in protein content and PLA2 activity of Crotalus molossus molossus venom from captive and wild specimens - Macías-Rodríguez, Eduardo Francisco; Díaz-Cárdenas, Cinthia Osmara; Gatica-Colima, Ana Bertha; Plenge-Tellechea, Luis Fernando (Acta Universitaria, 2014)
Envenomation by rattlesnake bites is medical imperative. Medicine focuses on diverse factors such as climate, age, sex, distribution, season of the year and diet, as these make the snake’s venom more poisonous and toxic. The objective of this study is to provide information on the seasonal variation of the protein content and hemolytic damage of the venom produced by captive and wild Crotalus molossus molossus. For this, we analyzed 16 samples of venom using the colorimetric method and visualized by Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE). The hemolytic activity of the phospholipase A2 (PLA2) was evaluated on erythrocytes-agar plates.We observed a large variation in the protein content between captive and wild snake venom; the winter pool of wild snake venom stands out with the highest concentration at 697 μg/μl ± 5.9 μg/μl, followed by the autumn pool in captivity with 648 μg/μl ± 20.8 μg/μl, the spring pool in captivity 528.51 μg/μl ± 10.59 μg/μl, and, lastly, the summer pool in captivity 1 with 387.9 μg/μl ± 5.6 μg/μl. The PLA2 was purified from the venom obtained from independent fractions 27, 39, 26, and 27 (n=60) of spring, summer, autumn and winter, respectively. The autumn sample showed higher hemolytic activity and the lowest activity was shown in the winter sample. We conclude that venom samples from captive rattlesnakes showed higher concentrations of protein compared to samples from wild snakes, in addition there were variations in the hemolytic activity according to the time of year.